Upaya Pembinaaan Keagamaan Remaja di Nagori Manik Maraja - Rizki Muhammad Haris; Nurhafifah Saragih; Tryana Ramadhany Batubara; Afifah Aulia Khoirunisa (Reslaj : Religion Education Social Laa Roiba Journal, 2023)
The Real Work Lecture (KKN) conducted by UIN SU students group 188 is a community service which aims to solve problems that exist in the community. Not only for the community but also for students, where students are able to learn from the experiences received and are able to learn more about the current state of society. This activity is able to see how big the role of students in Community Service activities in religious development and is expected to develop social competence and student personality competence. Methods of data collection is done by means of observation, interviews and use of technology. By using this method, students are expected to be able to see their potential and be able to implement it in activities. Keywords: Real Work Lecture (KKN), Religious Development, Youth